PATIENTS WITH COCHLEAR IMPLANTS IN THE OR – ISSUES AND CONCERNS - Blakley, Brian (Operating Room Nurses Association of Canada Journal, 2011)
Safety standards for patients with cochlear implants are difficult to find. Safety standards are, in fact, constantly evolving as more information becomes available. This article provides an overview of current philosophies and guidelines for most medical/surgical interventions, with emphasis on the operating room environment, as indicated by the three manufacturers authorized to market cochlear implants in Canada.